The Bionomics of the Teak Skeletoniser, Paliga Damastesalis Walker (Lepidoptera: Crambidae) and its Defoliation Impact on Young Teak, Tectona Grandis Linnaeus - Grace, Tabitha Lim Wui Oi (2004)
The distribution and feeding behaviour of a teak skeletoniser, Paliga damastesalis Walker, and the impact of its defoliation on the growth of young teak was investigated in a series of laboratory and field studies in Malaysia. A laboratory study on feeding behaviour showed that instar II to V larvae of P. damastesalis significantly preferred consuming leaf disks cut from young, expanding leaves of nodes 1 to 2 on two year-old trees, instead of leaf disks cut from mature, fully expanded leaves of nodes 3 to 5. Also, larvae that were confined to young leaves on pollarded two year-old trees a field study, fed and developed normally on those whole young leaves, indicating that secondary metabolites present in young whole leaves do not deter feeding or retard the growth of this insect significantly. Additionally, in that field study, larvae that were caged over mature leaves consumed a significantly larger leaf area in the fifth instar and had a significantly longer larval period than larvae caged over young leaves, while adult dry weights were not significantly different than that of larvae caged over young leaves. This indicates that P. damastesalis may be able to compensate for lower nutritional leaf content by feeding longer and increasing consumption of the nutrient-poor leaves. The findings of the laboratory study on the preference of P. damastesalis for younger leaves were supported by a subsequent study on the within-tree distribution of the immature stages on 6 to 12 month-old teak planted along a highway. The larvae were strongly associated with the upper node leaves in the field, which are comparatively younger than the lower node leaves, suggesting that the larvae preferred and actively sought younger leaves to consume. However, oviposition behaviour may also have influenced larval distribution as the larvae may have completed their development on or not far from the eggs were laid. Since over 60% of the larvae were found on leaves of nodes two to four, sampling of leaves from these nodes was recommended for young teak grown in similar conditions, during non-outbreak periods. On another note, a skewed sex ratio with males consistently forming less than 3.5% of the samples was reported, and it was suggested that a pathogen causing male mortality in the embrogenic stage of P. damastesalis may be exerting an influence on those field populations of the insect. In a ten-month study on the impact of P. damastesalis defoliation on the growth of six month-old teak in a plantation environment, severity of defoliation showed a significant negative assocation with production of new leaves and relative growth rates for tree height and tree collar diameter, only for the first two months after the defoliation. For the remainder of the study there was no difference in the growth of the trees in relation to the level of defoliation they experienced.